Liquid Body Wash Formulation with the Addition of Agarwood Leaf Extract - Faizah Hamzah; Ultri; Dewi Fortuna Ayu; Angga Pramana (Industria: Jurnal Teknologi dan Manajemen Agroindustri)
This study aimed to study the effect of agarwood leaf extract extracted through maceration as an antibacterial agent on the quality of liquid body wash. The study used a completely randomized design with five treatments and four replications. The treatments applied included the addition of agarwood leaf extract with concentrations of 0% (S1), 2.5% (S2), 5% (S3), 7.5% (S4), and 10% (S5). Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan's Test at 5% significance level. The results showed that adding agarwood leaf extract significantly affected free alkali, pH, foam stability, density, antibacterial activity, and sensory properties of liquid body wash. Liquid body wash with a 10% addition of agarwood leaf extract showed the best quality, with an inhibition zone of 24.86 ± 0.79 mm and 22.16 ± 2.40 mm against Bacillus subtilis and Pseudomonas aeruginosa. This liquid body wash has a free alkali content of 0.027%, a specific gravity of 1.08±0.08g/mL, foam stability of 89.79±0.77%, pH of 9.33±0.03, and does not cause skin irritation. Descriptive tests showed that the liquid body wash was dark brown with a distinctive aroma of agarwood leaves.